A Textbook Analysis of â€œMy Next Wordsâ€ for the Fifth Grade Elementary School - Novianti, Pipit; Ambarwati, Evi Karlina (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2023)
Textbooks are one of the materials used in the teaching and learning process. Textbooks have many benefits and important components in achieving the goals of the needs of learners (Cunningsworth, 1995). A qualitative method was conducted in this study. In brief, a descriptive qualitative research design was used to analyze and investigated an English textbook entitled Studentâ€™s Book â€œMy Next Wordsâ€ for Elementary School published by the Ministry of Education and Culture. The research data were collected from the content of the English textbook. To reveal the English textbook's content and appropriateness, this present study explored and researched an English textbook entitled Studentâ€™s Book "My Next Words" for Elementary School that applied Merdeka Curriculum. Following the BSNP (2017) criteria, the textbook was appropriate for use in the teaching and learning process, particularly in teaching English to Young Learners. Even though the textbook was considered appropriate in all aspects, some aspects of the book could be improved.